Dental Pulp Cells Isolated from Teeth with Superficial Caries Retain an Inflammatory Phenotype and Display an Enhanced Matrix Mineralization Potential - Alkharobi, Hanaa; Beattie, James; Meade, Josie; Devine, Deirdre; El-Gendy, Reem (Frontiers in Physiology, 2017)
We have isolated dental pulp cells (DPCs) from three healthy (hDPCs) and three carious (cDPCs) donors and shown that compared to hDPCs cells isolated from superficial carious lesions show higher clonogenic potential; show an equivalent proportion of cells with putative stem cell surface markers; show enhanced matrix mineralisation capability; have enhanced angiogenic marker expression and retain the inflammatory phenotype in vitro characteristic of superficial caries lesions in vivo. Our findings suggest that cDPCs may be used for further investigation of the cross talk between inflammatory, angiogenic and mineralisation pathways in repair of carious pulp. In addition cells derived from carious pulps (almost always discarded) may have potential for future applications in mineralized tissue repair and regeneration.